Role of diagnostic laparoscopy in patients with suspicion of colorectal peritoneal metastases to evaluate suitability for cytoreductive surgery with hyperthermic intraperitoneal chemotherapy. Issue 6 (18th September 2019) - Hentzen, J. E. K. R.; van der Plas, W. Y.; Constansia, R. D. N.; Been, L. B.; Hoogwater, F. J. H.; van Ginkel, R. J.; van Dam, G. M.; Hemmer, P. H. J.; Kruijff, S.
Abstract : Background: The aim of the present study was to determine the feasibility and safety of performing diagnostic laparoscopy (DLS) routinely in patients with suspicion of colorectal peritoneal metastases (PM) to evaluate suitability for cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS + HIPEC). Methods: Data for consecutive patients who underwent DLS between 2012 and 2018 were extracted retrospectively from an institutional database. The primary outcome was the degree of visibility of the abdominal cavity during DLS. Good laparoscopic evaluation of the abdominal cavity was defined as visibility of at least the regions of the diaphragm, pelvis and small bowel. Secondary outcomes were reasons for perioperative exclusion for CRS + HIPEC, major postoperative complications (Clavien–Dindo grade III or above) and difference in overall survival (OS) between patients deemed suitable or unsuitable for CRS + HIPEC. Kaplan–Meier analyses were performed. Results: Some 184 patients were analysed. Good laparoscopic evaluation was possible in 138 patients (75·0 per cent), and 24 (13·0 per cent) had conversion to an open procedure. Ninety‐three patients (50·5 per cent) were excluded for CRS + HIPEC, most commonly because of absence of colorectal PM (34 patients, 37 per cent) or extensive disease (Peritoneal Cancer Index 20 or above) (33 patients, 35 per cent). Major complications occurred in five patients (2·7 per cent), with no postoperative deaths. Median OS was significantly decreased in patients who were excluded due to extensive disease (14 (95 per cent c.i. 10 to 18) months) compared with patients suitable for CRS + HIPEC (36 (27 to 45) months) ( P  < 0·001). Conclusion: Routinely performing DLS in patients with suspicion of colorectal PM to evaluate suitability for CRS + HIPEC is feasible and safe, avoiding the morbidity of an unnecessary laparotomy in patients with extensive disease. Abstract : Diagnostic laparoscopy in the preoperative workup for cytoreductive surgery with hyperthermic intraperitoneal chemotherapy is feasible and safe in patients with suspicion of colorectal peritoneal metastases (PM). Exploratory laparotomy can be omitted for patients with extensive disease, who should not undergo unnecessary interventions, or for patients with no colorectal PM. Laparoscopic evaluation is feasible Abstract : Antecedentes: El objetivo del presente estudio fue determinar la viabilidad y seguridad de realizar una laparoscopia diagnóstica ( diagnostic laparoscopy, DLS) de rutina en pacientes con sospecha de metástasis peritoneal ( peritoneal metastasis, PM) de origen colorrectal para evaluar la idoneidad para la cirugía citorreductora con quimioterapia intraperitoneal hipertérmica ( cytoreductive surge ry + hyperthermic intraperitoneal chem otherapy, CRS+HIPEC). Métodos: Los datos de los pacientes consecutivos que fueron sometidos a DLS entre 2012 y 2018 se obtuvieron retrospectivamente de una base de datos institucional. La visualización de al menos las regiones de los diafragmas, pelvis e intestino delgado se definió como una correcta evaluación laparoscópica de la cavidad abdominal. Los resultados secundarios fueron las complicaciones postoperatorias mayores (Clavien‐Dindo grado ≥ III), razones para la exclusión perioperatoria para CRS+HIPEC y diferencia en supervivencia global ( overall survival, OS) entre pacientes que se consideraron apropiados y no apropiados para CRS+HIPEC. Se realizaron análisis de Kaplan‐Meier y análisis de riesgos proporcionales. Resultados: Se analizaron 181 pacientes. En 138 pacientes (75, 0%) fue posible una adecuada evaluación laparoscópica, mientras que 24 casos (13%) fueron convertidos a un procedimiento abierto. Se excluyeron 93 (50, 5%) pacientes para CRS+HIPEC, más comúnmente por la ausencia de PM colorrectales (36, 6%) o enfermedad extensa (37, 6%). En cinco pacientes aparecieron complicaciones mayores (2, 7%), sin mortalidad postoperatoria. La mediana de la OS disminuyó de forma significativa en pacientes que fueron excluidos debido a enfermedad extensa (14 meses, i.c. del 95% 10‐18) en comparación con pacientes idóneos para CRS+HIPEC (35 meses, i.c. del 95% 30‐40, P < 0, 0001). Conclusión: La realización rutinaria de DLS en pacientes con sospecha de PM de origen colorrectal para evaluar la idoneidad de la CRS+HIPEC es viable y segura. La morbilidad de una laparotomía innecesaria puede prevenirse en pacientes con enfermedad extensa o ausencia de PM colorrectales.